Rhizoma Gastrodiae Water Extract Modulates the Gut Microbiota and Pathological Changes of P-TauThr231 to Protect Against Cognitive Impairment in Mice - Zhao, Wenbin; Wang, Jianhui; Latta, Maria; Wang, Chenyu; Liu, Yuheng; Ma, Wantong; Zhou, Zhongkun; Hu, Shujian; Chen, Peng; Liu, Yingqian (Frontiers in Pharmacology, 2022)
Gastrodiae Rhizoma and its active constituents are known to exhibit neuroprotective effects in Alzheimer’s disease (AD). However, the effect of Rhizoma Gastrodiae Water Extract (WERG) on AD and detailed mechanism of action remains unclear. In this study, the mechanism of action of WERG was investigated by the microbiome–gut–brain axis using a D-galactose (D-gal) / AlCl3-induced AD mouse model. WERG improved the cognitive impairment of D-gal / AlCl3 - induced mice. The expression level of p-Tau thr231 in WERG-H treatment group was decreased and p-Tau thr231 was found negative in hippocampal DG, CA1, CA3 regions. Here, the diversity and composition of the gut microbiota were analyzed by 16sRNA sequencing. WERG-H treatment had a positive correlation with Firmicutes, Bacilli, Lactobacillus johnsonii, Lactobacillus murinus, Lactobacillus reuteri. Interestingly, the Rikenellaceae-RC9-gut-group in gut increased in D-gal / AlCl3-induced mice, but the increased Lactobacillus johnsonii, Lactobacillus murinus, Lactobacillus reuteri reversed this process. This may be a potential mechanistic link between gut microbiota dysbiosis and P-Tau Thr231 levels in AD progression. In conclusion, this study demonstrated that WERG improved the cognitive impairment of AD mouse model by enriching gut probiotics and reducing P-Tau Thr231 levels.